2014
DOI: 10.1248/bpb.b13-00773
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Coupled Organic Cation Antiporter-Mediated Uptake of Apomorphine Enantiomers in Human Brain Capillary Endothelial Cell Line hCMEC/D3

Abstract: R( )-Apomorphine is a dopamine agonist used for rescue management of motor function impairment associated with levodopa therapy in Parkinson's disease patients. The aim of this study was to examine the role of proton-coupled organic cation antiporter in uptake of R( )-apomorphine and its S-enantiomer in human brain, using human endothelial cell line hCMEC/D3 as a model. Uptake of R( )-or S( )-apomorphine into hCMEC/D3 cells was measured under various conditions to evaluate its time-, concentration-, energy-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…A proton‐coupled organic cation transporter has been shown to be functionally expressed in hCMEC/D3 cells and in TR‐BBB13 cells and is known to be responsible for the in vitro uptake of the ionized forms of other organic cationic drugs such as tramadol , diphenhydramine , pyrilamine , oxycodone , memantine , nicotine and apomorphine . Higuchi et al have recently suggested that the predicted steady‐state brain interstitial concentration of memantine in human produced by the proton‐coupled organic cation antiporter could be sufficient for therapeutic efficacy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proton‐coupled organic cation transporter has been shown to be functionally expressed in hCMEC/D3 cells and in TR‐BBB13 cells and is known to be responsible for the in vitro uptake of the ionized forms of other organic cationic drugs such as tramadol , diphenhydramine , pyrilamine , oxycodone , memantine , nicotine and apomorphine . Higuchi et al have recently suggested that the predicted steady‐state brain interstitial concentration of memantine in human produced by the proton‐coupled organic cation antiporter could be sufficient for therapeutic efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…Higuchi et al have recently suggested that the predicted steady‐state brain interstitial concentration of memantine in human produced by the proton‐coupled organic cation antiporter could be sufficient for therapeutic efficacy . Furthermore, amantadine has been demonstrated to have extensive potency for modulating the proton‐coupled organic cation transporter . Interestingly, since the adamantane moiety is a very small molecule, it has been conjugated to compounds that are poorly absorbed into the CNS in order to create a brain‐directed lipid carrier with improved BBB permeability .…”
Section: Discussionmentioning
confidence: 99%
“…The net uptake asymmetry observed is similar to oxycodone BBB transport in rats, (Boström et al, 2006), which showed a net 3-fold asymmetry favoring rat brain ECF relative to unbound plasma concentrations. Subsequent in vitro studies with oxycodone (Okura et al, 2008)-as well as more recent in vitro transport or in situ brain perfusion studies with several other low molecular weight weakly basic drugs, such as apomorphine (Okura et al, 2014), clonidine (André et al, 2009), codeine (Fischer et al, 2010), diphenhydramine (Shimomura et al, 2013), and nicotine (Cisternino et al, 2013)-implicate a pH-dependent proton-coupled antiporter at the BBB (Gharavi et al, 2015). It is possible that this transporter may also apply to bupropion and hydroxybupropion.…”
Section: Bupropion and Hydroxybupropion Brain Pharmacokinetics 629mentioning
confidence: 99%
“…9,10 In addition to these transporters, it has been reported that proton-coupled organic cation (H þ /OC) antiporter functions at human and rodent BBB, 10,11 although the molecular entity involved has not been identified yet. This antiporter contributes to BBB transport of various weakly basic drugs, including oxycodone, 11 pyrilamine, 12 diphenhydramine, 13 apomorphine, 14 tramadol, 15 memantine, 16 and clonidine. 17 Thus, it appears to recognize bulky and lipophilic type II cations with amine structures.…”
Section: Introductionmentioning
confidence: 99%